Models of Concurrent Disorder Service: Policy, Coordination, and Access to Care - Wiktorowicz, Mary; Abdulle, Aber; Di Pierdomenico, Kaitlin; Boamah, Sheila A. (Frontiers in Psychiatry, 2019)
Abstract Background: Societal capacity to address the service needs of persons with concurrent mental health and substance-use disorders has historically been challenging given a traditionally siloed approach to mental health and substance-use care. As different approaches to care for persons with concurrent disorders emerge, a limited understanding of current models prevails. The goal of this paper is to explore these challenges along with promising models of coordinated care across Canadian provinces. Materials and methods: A scoping review of policies, service coordination and access issues was undertaken involving a review of the formal and grey literature from 2000-2018. The scoping review was triangulated by an analysis of provincial auditor general reports. Results: Models of concurrent disorders service were found to have evolved unevenly. Challenges related to the development of system-level networks that foster service coordination and policy accountability were found to inhibit integrated care. Conclusion: Emergent models of coordinated care were found to encompass regional networks, clinical information-sharing, cross-training, improved scope of care to include psychologists and align physician incentives with patient needs to better support patient care.